Guided Digital Empowerment: Strategies to Address the Digital Divide for Rural Youth in Rural Area - Wahyuni, Lilik; Sukmawan, Sony; Putri, Rekyan Regasari Mardi; Pinandita, Eggi Pur; Nirmalasari, Intan; Praminsya, Agam; Rosyidah, Dinda Inayatur (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2026)
Purpose: Rural youth face their most significant challenge when they try to access digital technology for their productive economic work because the digital divide continues to exist. The internet infrastructure in many rural areas has improved but people still lack digital skills and they fail to use online platforms for business purposes. This research study investigates how rural youth learn digital skills and assesses how structured digital training programs help them start online businesses and develop their rural-based businesses. Design/Methodology/Approach: The researchers conducted their study using a mixed-methods approach which included surveys and interviews and observations and document analysis that studied rural youth in Malang Regency Indonesia. The researchers used quantitative data to assess digital literacy and internet usage patterns while the qualitative data examined the obstacles and assistance systems that digital entrepreneurs face in their work. Findings: The research results demonstrate that people in the study area have sufficient internet access but they still use the internet for business activities at a low level. Digital platforms serve as content consumption tools for rural youth who do not use them to create content or market their products online. The main obstacles to progress include insufficient digital abilities combined with expensive internet access and missing mentorship and training resources. The combination of training and mentoring together with infrastructure development helps people to build their digital skills which leads to increased e-commerce entrepreneurship activities. Originality/Value/Novelty: The implementation of a complete empowerment framework needs cooperation between government authorities, internet service providers, village enterprises (BUMDES), and local citizens to achieve inclusive and sustainable digital advancements in rural areas.